A política pública APL e sua vinculação com os fundamentos teóricos do inovacionismo: limites e contradições - Vale, Arilson Pereira do (2015)
Public policies reveal and embody interests and demands of actors, social classes or coalitions that hegemonically influence State actions. Therefore, the State and its public policies express open conflicts by opting for certain demands, not contemplating others and even veiling underlying conflicts. It is one of the central objectives of this work to try to understand and analyze this dynamic in the formulation and implementation of the public policy directed to the Local Productive Arrangements (APLs).That is, to identify what were the values, interests and political and ideological convictions that guided the proposition of APLs by the federal government and specifically the government of Paraná, as a public policy of regional development in the context of the 2000s? For this research we make use of theoretical frameworks of Science Technology and Society(STS) field of study and some basic concepts of "critical theory of technology" proposed by Andrew Feenberg. The hypothesis we seek to confirm is the narrow theoretical and methodological linking APL public policy with the fundamentals of inovacionismo and neoliberal policies. As a result of research, from the explanation and verification of this relationship contemplated in our case, we have developed analysis that seeks to demonstrate the limits and contradictions of APL public policy in their understanding and perspective on development and social inclusion.